Turkey’s Energy Transition Milestones and Challenges - World Bank (Washington, DC, 2015)
Through a variety of interlinked measures, Turkey’s energy reforms have achieved energy security for a fast-growing economy with rapidly increasing energy needs. These measures include legislation regarding electricity, gas, renewable energy, and energy efficiency; the establishment of an energy sector regulatory authority; energy price reform; the creation of a functional electricity market and large-scale introduction of natural gas; the restructuring of state-owned energy enterprises; and large-scale private sector participation through privatization and new investment. The objectives of this are to: (a) inform future energy reforms and reformers seeking to learn and benefit from Turkey’s experience, and (b) contribute to the dialogue on future energy reforms in Turkey. The report will present Turkey’s accomplishments in developing and implementing market-oriented energy reforms as well as selected key reform challenges going forward. In terms of reform milestones, the primary focus is on the electric power and natural gas sectors, although energy pricing and subsidies in the petroleum sector are also addressed. The report covers mainly the period starting from 2001, when progressive electricity and natural gas market laws were enacted, though the preceding period - from the opening of the energy sector to private investment in 1984 up to the enactment of the new energy market laws in 2001 - is covered briefly to present key milestones and to highlight key lessons. In terms of future challenges, the report discusses the ongoing and unfinished liberalization of the electricity and gas markets as well as required government support, including governance, in the energy sector. The challenges include the reform of the natural gas market, further development of the electricity market, and governance issues in the energy sector. Discussion of environmental and social issues and challenges has been integrated into the relevant sections.